84.3k views
0 votes
F(x)=-4(x-3)^2+7 can some one solve this quickly

F(x)=-4(x-3)^2+7 can some one solve this quickly-example-1
User Tom Weiss
by
6.0k points

2 Answers

2 votes

Answer:

y = -4x^2 +24x - 29

Explanation:

Standard notation

User Sebastian Thomas
by
4.9k points
5 votes


\bf f(x) = -4(x-3)^2+7\implies f(x) = -4(x-3)(x-3)+7 \\\\\\ f(x) = -4(\stackrel{\mathbb{F~O~I~L}}{x^2-6x+9})+7\implies f(x) = (-4x^2+24x-36)+7 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill f(x) = -4x^2+24x-29~\hfill

User Hung Luu
by
4.8k points